Memory and memories: An interdisciplinary approach - Amalia Calinescu (TRANSBAHASA, 2021)
Only humans seem to have the ability to project themselves into their past or future. This mental phenomenon, called autonoetic consciousness, proves the interrelation of memory, imagination, emotion, intelligence and consciousness as a way of creating self-images. The current paper constitutes an integrative study on memory from a theoretical perspective. The first part presents the most known neuroscientific viewpoints on the memory process, along with the pathological case of patient HM, who lost his memory following the removal of his hippocampus. The second part provides a humanistic perspective on recollection to demonstrate its compatibility with the neurological processes of storing information and forming memories. The final part conveys the phenomenon of recollection from the perspective of identity crisis in Kazuo Ishiguro’s novels, as a case study in memory literature. According to memory theories to date, identity cannot exist outside the process of recording and recalling past experiences. Despite the fallible nature of recollection, human beings return to their past in order to give a healthy meaning to their present.